Огляд основних проблем тривимірної графіки - Єнацький, О. О. (ХНУРЄ, 2016)
3D-dimensional graphics can use in system technical vision for rating deformation and normalization image.
Keywords: тривимірна графіка; 3D-dimensional graphics